Reciprocating internal combustion engines : performance Part 1. Standard refrence conditions and declarations of power - British Standards Institution (London BSI, 1977)
Reciprocating engines, Internal combustion engines, Prime movers, Performance, Power (mechanics), Fuel consumption, Lubricating oils, Declarations, Rated power, Pressure measurement (fluids), Formulae (mathematics)
Revised, Withdrawn
Cross References BS 5514:Part 2, BS 5514:Part 4, BS 5514:Part 6, BS 5555, BS 5672, BS 5673, BS 5676, ISO 1585, ISO 2534
Replaced By BS 5514-1:1982
Keywords: Engines -- Standards